2017
DOI: 10.3382/ps/pex153
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning and disinfection programs against Campylobacter jejuni for broiler chickens: productive performance, microbiological assessment and characterization

Abstract: Detailed cleaning and disinfection programs aims to reduce infection pressure from microorganisms from one flock to the next. However, studies evaluating the benefits to poultry performance, the sanitary status of the facilities, and the sanitary quality of the meat are rarely found. Thus, this study was designed to evaluate 2 cleaning and disinfecting programs regarding their influence on productive performance, elimination of Campylobacter, and characterization of Campylobacter jejuni strains when applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
6

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
(67 reference statements)
0
13
0
6
Order By: Relevance
“…A related study (Battersby et al, 2016b) found viable Campylobacter organisms in staff access areas of houses just before flock placement, but not from bird accommodation. Burbarelli et al (2017) examined environmental contamination following an enhanced C&D regime in an experimental facility; they reported that Campylobacter was still recovered from water in the drinker supply despite flushing the system with disinfectant. Follow-on flocks were similarly colonized by Campylobacter regardless of whether enhanced or control C&D techniques were used.…”
Section: The Rearing Phasementioning
confidence: 99%
See 1 more Smart Citation
“…A related study (Battersby et al, 2016b) found viable Campylobacter organisms in staff access areas of houses just before flock placement, but not from bird accommodation. Burbarelli et al (2017) examined environmental contamination following an enhanced C&D regime in an experimental facility; they reported that Campylobacter was still recovered from water in the drinker supply despite flushing the system with disinfectant. Follow-on flocks were similarly colonized by Campylobacter regardless of whether enhanced or control C&D techniques were used.…”
Section: The Rearing Phasementioning
confidence: 99%
“…Furthermore, there is some evidence that poultry-related strains commonly are exceptionally tolerant of aerobic conditions (O'Kane & Connerton, 2017;Oh, McMullen, & Jeon, 2015). They can be surprisingly persistent in certain environmental niches, including in drinking water supplies, and when colocated with other micro-organisms such as in biofilms or protozoal hosts (Agunos et al, 2014;Bronowski et al, 2014;Burbarelli et al, 2017;Humphrey et al, 2012;Whiley, van den Akker, Giglio, & Bentham, 2013). This, together with a wide range of host species that allow multiplication and shedding, presents a persistent environmental reservoir to challenge biosecurity and hygiene defenses.…”
mentioning
confidence: 99%
“…El objetivo principal en las naves de engorde consiste en asegurar que al inicio del ciclo productivo, las instalaciones se encuentren libres de microorganismos patógenos (Orihuel et al, 2015). Este tipo de prácticas preventivas son fundamentales en los programas de bioseguridad (de Castro et al, 2017) y para que resulten eficaces es imprescindible que, tanto la técnica utilizada como los productos empleados, sean los más adecuados y de calidad probada (Maertens et al, 2018).…”
Section: Descontaminación Limpieza Y Desinfecciónunclassified
“…En primer lugar, se lleva a cabo la limpieza de la nave y las instalaciones, para lograr la eliminación más completa posible de los residuos, tanto de las instalaciones como de los equipamientos, con el propósito de que el desinfectante pueda realizar su función correctamente (Ward et al, 2006), siendo para ello necesario adecuar el producto utilizado al tipo de suciedad. En función de su pH, los detergentes pueden ser alcalinos, ácidos o neutros; los primeros son los más indicados para la eliminación de residuos orgánicos, mientras que los ácidos actúan principalmente frente a materias minerales y los neutros se suelen utilizar en superficies delicadas, con pocos residuos adheridos (de Castro et al, 2017). En esta etapa, se deben humedecer abundantemente todas las superficies con la solución limpiadora, que luego tendrá que ser eliminada con abundante agua, una vez se haya reblandecido la suciedad (Orihuel et al, 2015).…”
Section: Descontaminación Limpieza Y Desinfecciónunclassified
See 1 more Smart Citation